Inhibiting ULK1 kinase decreases autophagy and cell viability in high-grade serous ovarian cancer spheroids - Singha, Bipradeb (Am J Cancer Res, 2020)
Metastasis in high-grade serous ovarian cancer (HGSOC) occurs through an unconventional route that involves exfoliation of cancer cells from primary tumors and peritoneal dissemination via multicellular clusters or spheroids. Previously, we demonstrated autophagy induction in HGSOC spheroids grown in vitro and in spheroids collected from ovarian cancer patient ascites; thus, we speculate that autophagy may contribute to spheroid cell survival and overall disease progression. Hence, in this study we sought to evaluate whether ULK1 (unc-51-like kinase-1), a serine-threonine kinase critical for stress-induced autophagy, is important for autophagy regulation in HGSOC spheroids. We demonstrate that HGSOC spheroids have increased ULK1 protein expression that parallels autophagy activation. ULK1 knockdown increased p62 accumulation and decreased LC3-II/I ratio in HGSOC spheroids. In addition, knocking down ATG13, a protein that regulates ULK1 activity via complex formation, phenocopied our ULK1 knockdown results. HGSOC spheroids were blocked in autophagic flux due to ULK1 and ATG13 knockdown as determined by an mCherry-eGFP-LC3B fluorescence reporter. These observations were recapitulated when HGSOC spheroids were treated with an ULK1 kinase inhibitor, MRT68921. Autophagy regulation in normal human fallopian tube epithelial FT190 cells, however, may bypass ULK1, since MRT68921 reduced viability in HGSOC spheroids but not in FT190 cells. Interestingly, ULK1 mRNA expression is negatively correlated with patient survival among stage III and stage IV serous ovarian cancer patients. As we observed using established HGSOC cell lines, cultured spheroids using our new, patient-derived HGSOC cells were also sensitive to ULK1 inhibition and demonstrated reduced cell viability to MRT68921 treatment. These results demonstrate the importance of ULK1 for autophagy induction in HGSOC spheroids and therefore justifies further evaluation of MRT68921, and other novel ULK1 inhibitors, as potential therapeutics against metastatic HGSOC.